Biological properties of two enantiomorphic forms of N‐(2, 6‐dimethylphenyl)‐4‐hydroxy‐2, 2‐dioxo‐1H‐2λ6, 1‐benzothiazine‐3‐carboxamide, a structural analogue of piroxicam. Issue 1 (10th December 2019) - Shishkina, Svitlana V.; Ukrainets, Igor V.; Vashchenko, Olga V.; Voloshchuk, Natali I.; Bondarenko, Pavlo S.; Petrushova, Lidiya A.; Sim, Galina
Abstract : Two enantiomorphic crystal forms of N ‐(2, 6‐dimethylphenyl)‐4‐hydroxy‐2, 2‐dioxo‐1 H ‐2λ 6, 1‐benzothiazine‐3‐carboxamide have been crystallized from different solvents. A pharmacological study showed that one possesses a high analgesic activity, while the other revealed a strong anti‐inflammatory activity. The ability to become a stereogenic centre due to the non‐equivalence of its O atoms in hydrogen‐bond formation is a property of the ring sulfonyl group. Abstract : The title benzothiazine‐3‐carboxamide, C17 H16 N2 O4 S, crystallized in two enantiomorphic crystal forms with the space groups P 32 and P 31 despite the absence of a classic stereogenic atom. The molecular structures are mirror images of each other. Only one sulfonyl O atom takes part in intramolecular hydrogen bonding as a proton acceptor and this atom is different in the two enantiomorphic structures. As a result, the S atom becomes a pseudo‐stereogenic centre. This fact is worth taking into account due to the different biological activities of the enantiomorphic forms. One form possesses a high analgesic activity, while the other form revealed a high anti‐inflammatory activity.